ANALISIS ANALISIS COST PLUS PRICING DALAM MENENTUKAN HARGA JUAL PRODUK PADA WARUNG GEPREKAN BU TIK DI KEDIRI - Yenny Meilina Soesilowati; Erna Puspita; Sugeng (Jurnal Manajemen, Ekonomi, Keuangan dan Akuntansi, 2023)
Cost Plus Pricing analysis is used to determine the selling price of the product at Bu Tik's geprekan stall in Kediri. The purpose of this research is to use cost plus pricing analysis to determine the selling price of the product at Warung Geprekan Bu Tik in Kediri. This method takes into account production costs and operational costs and adds a profit margin to determine the appropriate selling price. The results of this analysis indicate that the selling price which is determined using cost plus pricing can increase Warung Geprekan Bu Tik's revenue and provide stable profits for stall owners.